The Study of Knowledge and Wisdom of Folk Medicine in Thai Folk Doctors, Tak Province - วรปาณิ, ธีรยา; วรปาณิ, ปองพล (Community and Social Development Journal, 2018)
Abstract The objective was to study the knowledge and wisdom patterns and procedures for treating patients by Thai folk doctors in Tak Province. This study were mixed method studies. 14 Thai folk doctors from Pobpra and Thasongyang districts in Tak province were selected to study by purposive sampling from January 1, 2016 to November 30, 2016. The results revealed that 5 and the experts in holy water, 4 are the experts in herbal medicines as 35.72 and 28.57 percent, respectively. However, for the 3 Thai folk doctors 1 was the herbal medicine and orthopedic doctor, 1 was the herbal medicine the and holy water doctor and 1 was the herbal medicine and acupuncture doctor. Presently, only 21.43 percent of the Thai folk doctors work with government offices, such as hospitals, schools and temples to educate people and students about folk medicines and herbal medicines. However, most Thai folk doctors don’t pass on their knowledge to their descendants and disciples due to the lack of the appropriate successors and no records. In the future, collecting and documenting the knowledge in Thai folk medicines can preserve Thai folk medicines and wisdom.